The Effects of 16 Weeks of Exercise Training on Neutrophil Functions in Breast Cancer Survivors - Bartlett, David B.; Hanson, Erik D.; Lee, Jordan T.; Wagoner, Chad W.; Harrell, Elizabeth P.; Sullivan, Stephanie A.; Bates, Lauren C.; Alzer, Mohamdod S.; Amatuli, Dean J.; Deal, Allison M.; Jensen, Brian C.; MacDonald, Grace; et al. (Frontiers in Immunology, 2021)
Following therapy, breast cancer survivors (BCS) have an increased risk of infections because of age and cancer dysregulation of inflammation and neutrophil functions. Neutrophil functions may be improved by exercise training, although limited data exist on exercise and neutrophil functions in BCS.Sixteen BCS [mean age: 56 (SD 11) years old] completed 16 weeks of community-based exercise training and a 45-minute acute bout of cycling before (Base) and after (Final) the exercise training program. Exercise training consisted of 3 x 40 – 60 minute mixed mode aerobic exercises, comprising 10 – 30 minutes aerobic and 30 minutes resistance training. At Base and Final, we took BCS blood samples before (PRE), immediately after (POST), and 1 hour after (1Hr) acute exercise to determine neutrophil counts, phenotype, bacterial killing, IL-6, and IL-8 levels. Eleven healthy, age- and physical activity levels-matched women (Control) completed the acute bout of exercise once as a healthy response reference. Resting Responses. BCS and Controls had similar Base PRE absolute neutrophil counts [mean (SD): 3.3 (1.9) v 3.1 (1.2) x 109/L, p=0.801], but BCS had lower bacterial phagocytosis [3991 (1233) v 4881 (417) MFI, p=0.035] and higher oxidative killing [6254 (1434) v 4709 (1220) MFI, p=0.005], lower CD16 [4159 (1785) v 7018 (1240) MFI, p<0.001], lower CXCR2 [4878 (1796) v 6330 (1299) MFI, p=0.032] and higher TLR2 [98 (32) v 72 (17) MFI, p=0.022] expression, while IL-6 [7.4 (5.4) v 4.0 (2.7) pg/mL, p=0.079] levels were marginally higher and IL-8 [6.0 (4.7) v 7.9 (5.0) pg/mL, p=0.316] levels similar. After 16 weeks of training, compared to Controls, BCS Final PRE phagocytosis [4510 (738) v 4881 (417) MFI, p=0.146] and TLR2 expression [114 (92) v 72 (17) MFI, p=0.148] were no longer different. Acute Exercise Responses. As compared to Controls, at Base, BCS phagocytic Pre-Post response was lower [mean difference, % (SD): 12% (26%), p=0.042], CD16 Pre-Post response was lower [12% (21%), p=0.016] while CD16 Pre-1Hr response was higher [13% (25%), p=0.022], TLR2 Pre-Post response was higher [15% (4%) p=0.002], while IL-8 Pre-Post response was higher [99% (48%), p=0.049]. As compared to Controls, following 16 weeks of training BCS phagocytic Pre-Post response [5% (5%), p=0.418], CD16 Pre-1Hr response [7% (7%), p=0.294], TLR2 Pre-Post response [6% (4%), p=0.092], and IL-8 Pre-Post response [1% (9%), p=0.087] were no longer different. Following cancer therapy, BCS may have impaired neutrophil functions in response to an acute bout of exercise that are partially restored by 16 weeks of exercise training. The improved phagocytosis of bacteria in BCS may represent an exercise-induced intrinsic improvement in neutrophil functions consistent with a reduced risk of infectious disease. Clinical Trial Registration ClinicalTrials.gov, identifier NCT03760536.